PELUANG DAN TANTANGAN KEPEMIMPINAN INDONESIA DALAM BIDANG POLITIK-KEAMANAN DI ASEAN PADA KRISIS POLITIK MYANMAR TAHUN 2021 - Angga Nurdin Rachmat (Universitas Jenderal Ahmad Yani, 2022)
Indonesia has credibility in carrying out its leadership role in the political-security sector in ASEAN. The political crisis that occurred in Myanmar due to a military coup in early 2021 raised concerns that it would have an impact on regional stability and ASEAN solidity. This reality makes researchers question what are the hopes and challenges of Indonesia in carrying out political-security leadership in ASEAN in the political crisis in Myanmar? This research was conducted with a qualitative design using secondary data from various literatures. This study finds that in responding to the crisis that occurred in Myanmar, Indonesia is faced with hopes for ideas and efforts that are always in helping to find solutions as part of the implementation of leadership in the security-politics field that comes from free-active foreign policy, transition experience democracy and capabilities. democracy. But on the other hand, Indonesia must also be faced with challenges that must be faced in the capacity to carry out political-security leadership originating from the ASEAN Way, rejection of the people of Myanmar and the inconsistency of human rights issues as well as the consolidation of domestic politics in responding to the crisis. Therefore, Indonesia still has to engage in constructive engagement through strengthening its democracy and human rights agenda and prioritizing non-megaphone diplomacy as part of efforts to help Myanmar out from the political crisis.